A Collaborative Approach to Eliminating Street Drug Markets through Focused Deterrence - Di Luca, Kristen (2009)
This report presents the evaluation process and findings from the grant, A Collaborative Approach to Eliminating Street Drug Markets through Focused Deterrence. This action research was conducted by a team of researchers from The University of North Carolina at Greensboro‘s Center for Youth, Family, and Community Partnerships, the University of Notre Dame, and the Winston-Salem State University Center for Community Safety from January 2007 through December 2008